Physical and Social-Motivational Contextual Correlates of Youth Physical Activity in Underresourced Afterschool Programs. (August 2015) - Zarrett, Nicole; Sorensen, Carl; Cook, Brittany Skiles
Afterschool programs (ASPs) have become increasingly recognized as a key context to support youth daily physical activity (PA) accrual. The purpose of the present study was to assess the physical and social-motivational climate characteristics of ASPs associated with youth PA, and variations in contextual correlates of PA by youth sex. Systematic observations of 7 ASPs serving underserved youth (minority, low income) was conducted using the System for Observing Play and Leisure Activity in Youth and a social-motivational climate observation tool founded on self-determination theory. For five program days at each site, teams of two coders conducted continuous observations of youth PA (sedentary, moderate, vigorous), five physical features (e.g., equipment availability), eight staff interactions (e.g., encourage PA), and seven motivational climate components (e.g., inclusive). Aligned with previous research, regressions controlling for variations by site indicated that organized PA, provision of portable equipment, and staff PA participation and supervision are key correlates of youth PA. Moreover, as the first study to systematically observe motivational-context characteristics of ASPs, we identified several key modifiable motivational features that are necessary to address in order to increase youth engagement in PA during the out-of-school hours. Among motivational features assessed, "relatedness" components (positive peer relations, inclusive/cooperative activities) were primary correlates of girls' PA. In contrast, all three motivational features specified by self-determination theory (support for autonomy, mastery/competence, and inclusion/relatedness) were correlated with boys' PA. Findings are discussed in terms of policy and practice for understanding strengths and needs of ASPs to effectively engage youth in PA.